The examination of relationships between upper extremity joint lengths, reaction time and shoulder strength parameters in youth canoe athletes - Alparslan İnce; Muhammet Emirhan Çelik (Turkish Journal of Kinesiology)
The aim of this study was to investigate the relationships between upper extremity joint length, reaction time and shoulder strength in young canoe athletes. The study was carried out with the voluntary participation of 23 young canoe athletes. Within the scope of the research plan, height measurements, body weight measurements, length measurements of the upper extremities (arm and forearm length), arm span length measurements, reaction time measurements and isokinetic strength measurements of the athletes were carried out. The effect of joint length values on reaction time and shoulder strength parameters was examined by multiple linear regression analysis. The results show that joint length values have a significant effect on reaction time and shoulder strength values in canoe athletes (p